Clinical and molecular findings in patients with pattern dystrophy. (3rd September 2021) - Sodi, Andrea; Mucciolo, Dario Pasquale; Giorgio, Dario; Passerini, Ilaria; Pacini, Bianca; Bruschi, Mario; Verdina, Tommaso; Virgili, Gianni; Giansanti, Fabrizio; Murro, Vittoria
ABSTRACT: Purposes: To study the clinical and genetic background of a series of Italian patients affected by pattern dystrophy (PD). Methods: We reviewed patients with a clinical diagnosis of PD examined at the Eye Clinic in Florence from 2012 to 2019. We took into consideration patients with a standard ophthalmological examination, personal and familial ophthalmological history, fundus imaging, and molecular genetic analysis of genes PRPH2 and BEST1 . We labelled patients with BEST1 and PRPH2 mutations as m-PD group (mutated) whereas patients with no mutations in these 2 genes as nm-PD group (non-mutated). Results: Seventy-seven PD patients were assessed (average age 59.7 ± 14.2, range 31–88 years). Fifty patients were placed in the nm-PD group and 27 in the m-PD. Pathogenic BEST1 and PRPH2 mutations were detected in 7% and 22% of PD patients, respectively. In total, we reported 1 BEST1 and 8 PRPH2 novel mutations. Ten patients were characterized by drusen in the nm-PD group whereas in no patients in the m-PD group drusen were detected at the fundus. Conclusions: An important proportion of patients affected by PD showed BEST1 or PRPH2 mutations. Patients affected by drusen represent a different sub-phenotype. Genetic examination is recommended for a correct clinical management.